Guide reading : good first teaching for all children - FOUNTAS, Irene C.; Gay Su Pinnell (Portsmouth, NH : Heinemann, 1996)
"Addresses the learning characteristics, attitudes, and skill levels of college students. It is intended to equip them with the skills they need to handle the diverse reading demands of college coursework.
Includes bibliography and index
Keywords: Reading (Higher education) Study skills